Islam Kawasan Tuban Bumi Wali: The Spirit of Harmony - Janeko Janeko (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
This study aims to examine the history, process of Islamization, and the formation of the religious identity of Tuban Regency as the "Land of Saints". The method used is a historical research method with a qualitative approach through library studies of primary sources such as Serat Babad Thubban and Serat Babad Tanah Jawi, as well as secondary sources in the form of historical records of Tuban and other supporting literature. The results of the study indicate that the process of the entry of Islam in Tuban took place peacefully through trade, marriage, and cultural preaching carried out by the saints, especially Sheikh Ibrahim Asmoroqondi and Sunan Bonang. Islamic values ​​​​successfully assimilated with local culture, giving birth to a distinctive Islamic style of Tuban that is harmonious and tolerant. The transformation of Tuban's identity from "Kota Tuak" to "Land of Saints" reflects the successful internalization of Islamic spiritual values ​​​​in the social and cultural life of its people. With the concept of "The Spirit of Harmony", Tuban is now a symbol of inclusive and dynamic Islam, which combines religiosity, local wisdom, and national spirit in one unified value.